Significant Trends in the Development of Finnish Teacher Education Programs (1860-2010) - Satu Uusiautti (Education Policy Analysis Archives/Archivos Analíticos de Políticas Educativas, 2013)
The roots of teacher training in Finland extend to the 1860s. The evolution of teacher training was closely connected to the history of elementary education and changes in educational policy and the Finnish society. Recently, the Finnish educational system and its teacher education programs have fared extremely well in international comparisons. This raises a question concerning the kinds of initiatives and policies that this story has involved. This article will provide some answers, and it also discusses the trends and developmental aspirations that have molded the approaches to teacher training in this country. The article is based on Finnish research literature on teacher training and relevant contemporary developmental reports and laws. The main purpose is to provide a review of the historical development of Finnish teacher training—its significant achievements and the most crucial turning points—and then to discuss their contribution to the educational outcomes in the current system.